Mental health and wellbeing in the workplace : a practical guide for employers and employees - Hasson, Gill; Butler, Donna (Donna Margaret) (Wiley-Capstone, 2020)
"The Government's Department of Health advises that one in four of us will experience mental ill health at some point in our lives. It is therefore important that employers and their staff take steps to promote positive mental health and support those experiencing mental ill health. Wellbeing & Mental Health in the Workplace includes case studies from both employers and employees perspectives, and also covers the following issues: What is mental health?; Why is understanding mental health important; the impact on a business and the impact on an employee being able to do their job effectively; Promoting positive mental health in the workplace; the importance of a 'well being strategy' in the workplace; Managing staff experiencing mental ill health; Dealing with stress and anxiety in the workplace; Where to go for further support if you are experiencing mental ill health"--